An Empirical Model of Titan's Magnetic Environment During the Cassini Era: Evidence for Seasonal Variability. Issue 11 (7th November 2017) - Kabanovic, Slawa; Simon, Sven; Neubauer, Fritz M.; Meeks, Zachary
Abstract: Based on the magnetic field data collected during the Cassini era, we construct an empirical model of the ambient magnetospheric field conditions along the orbit of Saturn's largest moon Titan. Observations from Cassini's close Titan flybys as well as 191 nontargeted crossings of Titan's orbit are taken into account. For each of these events we apply the classification technique of Simon et al. (2010b) to categorize the ambient magnetospheric field as current sheet, lobe‐like, magnetosheath, or an admixture of these regimes. Independent of Saturnian season, Titan's magnetic environment around noon Saturn local time is dominated by the perturbed fields of Saturn's broad magnetodisk current sheet. Only observations from the nightside magnetosphere reveal a slow but steady change of the background field from southern lobe‐type to northern lobe‐type on a timescale of several years. This behavior is consistent with a continuous change in the curvature of the bowl‐shaped magnetodisk current sheet over the course of the Saturnian year. We determine the occurrence rate of each magnetic environment category along Titan's orbit as a function of Saturnian season and local time. Key Points: An empirical model of the ambient magnetic field conditions along Titan's orbit has been developed Cassini magnetic field data from 316 crossings of Titan's orbit between 2004 and 2017 are included Seasonal variability of the ambient magnetic field is discernible only in Saturn's nightside magnetosphere but not at the dayside